Trypanosoma brucei growth control by TNF in mammalian host is independent of the soluble form of the cytokine - Gilles Vanwalleghem (Nature Portfolio, 2017)
Abstract Infection of C57Bl/6 mice by pleomorphic African trypanosomes Trypanosoma brucei and T. congolense is characterized by parasitemia waves coupled with the production of systemic levels of TNF. This cytokine is known to control T. brucei growth, but also to contribute to tissue damage, shortening the survival time of infected mice. Using a dominant-negative version of TNF to discriminate between the effects of the membrane-form versus the soluble form of TNF, we show that the second form is involved in neither parasite control nor induction of liver injury. Therefore, soluble TNF is likely not a major contributor to disease outcome. We propose that membrane-bound TNF is responsible for both T. brucei control and host pathology.